2013
DOI: 10.1042/bj20121903
|View full text |Cite
|
Sign up to set email alerts
|

The CUL3–KLHL3 E3 ligase complex mutated in Gordon's hypertension syndrome interacts with and ubiquitylates WNK isoforms: disease-causing mutations in KLHL3 and WNK4 disrupt interaction

Abstract: The WNK (with no lysine kinase)–SPAK (SPS1-related proline/alanine-rich kinase)/OSR1 (oxidative stress-responsive kinase 1) signalling pathway plays an important role in controlling mammalian blood pressure by modulating the activity of ion co-transporters in the kidney. Recent studies have identified Gordon's hypertension syndrome patients with mutations in either CUL3 (Cullin-3) or the BTB protein KLHL3 (Kelch-like 3). CUL3 assembles with BTB proteins to form Cullin–RING E3 ubiquitin ligase complexes. To exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
225
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(237 citation statements)
references
References 38 publications
12
225
0
Order By: Relevance
“…Interestingly, S433 is recurrently mutated in autosomal dominant PHAII (4,26). Mutation of S433 abrogates WNK4 binding and degradation, increasing WNK4 levels (22,23). This observation suggested that S433 phosphorylation might modulate KLHL3 binding and degradation of WNK4.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, S433 is recurrently mutated in autosomal dominant PHAII (4,26). Mutation of S433 abrogates WNK4 binding and degradation, increasing WNK4 levels (22,23). This observation suggested that S433 phosphorylation might modulate KLHL3 binding and degradation of WNK4.…”
Section: Resultsmentioning
confidence: 95%
“…[16][17][18][19][20][21], and WNK4 function can be modulated by phosphorylation (21). CUL3/KLHL3 has been shown to target WNK4 and WNK1 for ubiquitination and degradation, and disease-causing mutations impair this binding and degradation (22)(23)(24). In particular, dominant mutations in the Kelch domain of KLHL3 prevent binding to WNKs; reciprocally, disease-causing point mutations in WNK4 also prevent WNK4-KLHL3 binding.…”
Section: Significancementioning
confidence: 99%
“…Interestingly, KLHL2 protein was also increased by Cul3 knockdown, suggesting that KLHL2 protein may be regulated by Cul3-based E3 ligase as shown for KLHL3. 5 However, such an increase of KLHL2 did not lead to a reduction in WNK3 protein under the Cul3 knockdown condition, clearly suggesting that Cul3 is necessary for KLHL2-mediated WNK3 degradation. AngII could still decrease KLHL2 under the Cul3 knockdown condition (Figure 7), suggesting that the increased degradation of KLHL2 by AngII may be independent of Cul3.…”
Section: Klhl2 Regulates Wnk3 Protein Levels In Movas Cellsmentioning
confidence: 96%
“…Each of them forms a complex with Cul3 and acts as E3 ligase on WNK1/WNK2/WNK3/ WNK4. [4][5][6]19,20 The KLHL3-Cul3 complex acts as an E3 ubiquitin ligase for WNK kinases, and KLHL3 mutations have been reported to cause PHAII through the impaired ubiquitination of WNK4. 4 However, the involvement of WNK kinase regulation by ubiquitination in the situation other than PHAII has not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Although mutations in Kelchlike 3 and Cullin-3 cause hyperkalemic hypertension that is reversible with thiazides, these proteins probably do not interact directly with NCC. Instead, Kelch-like 3 binds and ubiquitinates WNK4 and the subsequent degradation of WNK4 would be expected to increase NCC activity (Figure 3) [89,106,128,132].…”
Section: Ubiquitin Ligasesmentioning
confidence: 99%